Effects of preheat treatment on the physicochemical and interfacial properties of cod proteins and its relation to the stability of subsequent emulsions. (March 2021) - Ma, Wuchao; Wang, Jiamei; Wu, Di; Xu, Xianbing; Du, Ming; Wu, Chao
Abstract: Interests in cod proteins (CPs) in food industry are growing due to their high nutritional attributes and the largest fishing amount worldwide. However, CPs are usually consumed as low value-added products, and limited attention has been paid to their emulsifying properties. In this study, the effects of preheat treatment at different temperatures (70–100 °C) and time (5–60 min) on the physicochemical and interfacial properties of CPs were investigated. Results revealed that increasing the preheating temperature and time led to smaller particle size, lower contents of sulfhydryl sites, and higher surface hydrophobicity of CPs. Preheat treatment further significantly increased the ratios of CPs-absorption at the oil-water interface of emulsions that presented smaller droplet size and lower interfacial tension due to promoted surface active properties of CPs. Non-reducing SDS-PAGE showed that CPs at the interface were mainly composed of tropomyosin, actin, as well as disulfide bonds cross-linked moieties, which formed a highly viscoelastic film. The interfacial physical barrier hampered the coalescence of adjacent droplets, as verified by lower creaming index, which demonstrated the enhanced stability of preheated CPs-coated emulsions. The findings expand the application potential of CPs as promising emulsifiers by a straightforward preheat treatment. Graphical abstract: Image 1 Highlights: Preheating improved the emulsifying properties of cod proteins. Preheating promoted the adsorption of cod proteins at the interface. Preheating led to cod proteins with smaller size. Preheated cod proteins possessed larger unfolding extent.